“We Need to Talk…” Evolving Conversations about Wildlife Ethics in Hunting Media - Von Essen, Erica (Humanimalia, 2018)
Hunters are accustomed to a degree of “freedom with responsibility” and exemption from having to justify their practices to the general public. But the time for sovereignty may be over. Hunters increasingly have to justify their hunting forms, their shooting practices, the way they talk about wildlife and killing generally to the general public, which demands transparency about the ethical principles that guide interaction with wildlife—a public good. Such principles have always existed tacitly among hunters, but the community now observes a need to explicate them, in part, to justify the mantra of freedom with responsibility. In this study, hunting media across six decades past examined as to its evolving ethics talk. Hunting magazines, social media forum, and online pages are searched for the contours of ethics talk. Ten interviews with hunting journalists, six of whom editors of hunting magazines, relay the climate of ethics talk and the relative willingness or reluctance of hunters to engage in such discussions. It is shown that there are stronger calls to self-criticize and reflect on hunting ethics and across new nodes. The evolving nature of ethics discussions further reflects the historical modality (and context) in which they take place. Ethics talk is shown, for example, to be shaped by Sweden’s ascension into the EU, the rise of rapidly spreading potentially incriminating trophy shots across social media and a reaction toward processes of globalization. Among other things, discernible from the ethics talk is a re-activation of nationalist traditions around “jägarmässighet’ and Swedish propriety in the face of outside threat to identity.